Danger in Kashmir - Korbel, Josef (Book collections on Project MUSE., 1966)
An excellent presentation of the many complex factors which stem from the Kashmir dispute between India and Pakistan. The author as the original Czech member of the United Nations Commission for India and Pakistan, brings to his narrative first-hand experience. Originally published in 1954. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.